Empowering Students through Character Education to Overcome Bullying in English Language Teaching - Aini, Risti Nur; Mandarani, Vidya (Wadah Inovasi Indonesia, 2023)
This literature review explores the impact of character education in English Language Teaching (ELT) on mitigating school harassment. Addressing a gap in understanding its role, the study uses qualitative analysis to identify strategies such as integrating social skills, multicultural perspectives, and active student participation. Results highlight teachers' roles in fostering respect and honesty, while multicultural approaches combat stereotypes and promote diversity acceptance. Practical implications emphasize collaborative efforts among teachers, students, and parents, using methods like role-playing and discussions to ensure a safe, inclusive educational environment. This study underscores character education's importance in creating a positive school culture.